A subset of thalamocortical projections to the retrosplenial cortex possesses two vesicular glutamate transporter isoforms, VGluT1 and VGluT2, in axon terminals and somata. Issue 9 (19th April 2014) - Oda, Satoko; Funato, Hiromasa; Sato, Fumi; Adachi‐Akahane, Satomi; Ito, Masanori; Takase, Kenkichi; Kuroda, Masaru
ABSTRACT: Vesicular glutamate transporter isoforms, VGluT1–VGluT3, accumulate glutamate into synaptic vesicles and are considered to be important molecules in glutamatergic transmission. Among them, VGluT2 mRNA is expressed predominantly throughout the dorsal thalamus, whereas VGluT1 mRNA is expressed in a few thalamic nuclei. In the thalamic nuclei that project to the retrosplenial cortex (RSC), VGluT1 mRNA is expressed strongly in the anterodorsal thalamic nucleus (AD), is expressed moderately in the anteroventral and laterodorsal thalamic nuclei, and is not expressed in the anteromedial thalamic nucleus. Thus, it has been strongly suggested that a subset of thalamocortical projections to RSC possesses both VGluT1 and VGluT2. In this study, double‐labeled neuronal somata showing both VGluT1 and VGluT2 immunolabelings were found exclusively in the ventral region of AD (vAD). Many double‐labeled axon terminals were also found in two major targets of vAD, the rostral part of the reticular thalamic nucleus and layers Ia and III–IV of the retrosplenial granular b cortex (RSGb). Some were also found in layer Ia of the retrosplenial granular a cortex (RSGa). These axon terminals contain significant amounts of both VGluTs. Because the subset of thalamocortical projections to RSC has a unique molecular basis in the glutamatergic transmission system, it might play an important role in the higher cognitive functions processed in the RSC. Furthermore, double‐labeled axon terminals of a different type were distributed in RSGb and RSGa. Because they are small and the immunoreactivity of VGluT2 is significantly weaker than that of VGluT1, they seemed to be a subset of corticocortical terminals. J. Comp. Neurol. 522:2089–2106, 2014. © 2013 Wiley Periodicals, Inc. Abstract : Neuronal somata showing both VGluT1 and VGluT2 immunolabelings were found exclusively in the ventral region of AD (vAD), and double‐immunolabeled terminals were distributed in RSGb (arrowheads) and rRt, which are major targets of vAD. Double‐immunolabeled terminals of a different type were also found (arrows). They seemed to be corticocortical terminals.